Catholic Charismatic Renewal Movement and Secularization. (7th November 2014) - Alva, Reginald
Abstract : Advances in science and technology have relegated the space of religion in the society. Modern people have rightly challenged the traditional hegemony of religious institutions. However, challenging unjust practices within religious institutions must not systematically jeopardize the spiritual and ethical values, which the religions propose. Society should not sacrifice morality and values on the altar of science and progress. The Catholic Church held the Second Vatican Council (1962–5) with the aim of overall renewal and reformations within the church. It prepared the Church to read the signs of times. The beginning of the Charismatic Renewal in 1967 within the Catholic Church is a fruit of that effort. Surveys show that the Charismatic Movement had a phenomenal growth. In the year 2000, around 11.3 percent of the total global Catholic population was associated with Charismatic Movement.2 The Catholic Charismatic Renewal Movement (CCRM) seeks the grace of renewal to foster a deeper communion with God the Father, a total acceptance of the lordship of Jesus Christ and a perennial openness to the Holy Spirit. The CCRM is playing a vital role by infusing life and vigor to the Church, attracting youth to the Church, bringing hope to the overstressed people and help them discover the meaning of life in the midst of growing ennui and angst because of the rapture of the bubble economy and effects of secularization. The task of renewal of the whole Church is far from finished. It is a project in process. In this paper, we propose to trace the effects of this movement in the Catholic Church. We shall attempt to study, how best this movement can help in preserving the traditional religious values on the one hand and the progress of humanity on the other.